Enhancing Problem-Solving Abilities and Science Process Skills through Guided Inquiry with Laboratory Media in High School - Rahman, Sunarti; Muhammad Syahri; Agus Tinus (Universitas Muhammadiyah Makassar, 2025)
Physics education at the high school level continues to face challenges in cultivating students’ higher-order thinking, particularly problem-solving ability and science process skills, which are essential for scientific literacy and future learning. Conventional lecture-based approaches often result in passive learning and limited opportunities for inquiry, creating an urgent need for innovative teaching strategies. This study aimed to investigate the effectiveness of guided inquiry supported by laboratory media in enhancing problem-solving ability and science process skills among high school students. Employing a quasi-experimental design with a pretest–posttest nonequivalent control group, the research was conducted with 64 Grade X students at SMAN 1 Gowa, Indonesia, who were divided into an experimental group taught through guided inquiry with laboratory media and a control group receiving traditional instruction. Data were collected using a validated problem-solving test and a science process skills assessment and analyzed using descriptive statistics, independent samples t-tests, and normalized gain (N-gain) scores. The results indicated that the experimental group achieved significantly higher improvements, with N-gain scores of 0.70 (high) for problem-solving and 0.50 (medium) for science process skills, compared with 0.60 and 0.38, respectively, in the control group. These findings confirm that guided inquiry combined with laboratory media provides a more effective learning environment by promoting active engagement, conceptual understanding, and procedural competence. The novelty of this study lies in its focus on the measurement topic in high school physics, an area often associated with analytical difficulty. The study concludes that this instructional model contributes to the advancement of physics education by offering empirical evidence for curriculum innovation and pedagogical reform.